PELATIHAN PEMBUATAN MOL AKAR BAMBU DALAM MENDUKUNG PERTANIAN ORGANIK KEDELAI DI DESA JUBUNG KABUPATEN JEMBER - Aritonang, Firman; Pakpahan, Tioma Stephani; Harsanti, Restiani Sih; Fariroh, Indri; Usmadi, Usmadi; Munandar, Denna Eriani; Sundahri, Sundahri; Slameto, Slameto (PAPUMA: Journal of Community Services, 2025)
Jubung Village is the largest soybean producing area in Sukorambi District. The Farmer Group 'Tani Mulyo" experienced problems in soybean cultivation, namely soybean production which could not increase and the high price of fertilizer. The solution that can be given is the use of local microorganisms (MOL). MOL (Local Microorganisms) is a group of commonly cultivated microorganisms use in the "zero waste" concept is as a "starter" for organic composting. Materials and tools used were bamboo roots, granulated sugar, shrimp paste, rice bran, water, pan, stirrer, 20 L bucket, stove, cover and sprayer. The work program began with preparation of activities such as coordination with several stakeholders such as village officials, accompanying group lecturers, farmers and the Jubung village community. Next, socialization and practice of making local microorganisms (MOL) were carried out. This implementation is a practice of making local microorganisms (MOL) which is carried out at the home of one of the jubung farming communities. The production of local microorganisms (MOL) was accompanied by lecturers and carried out jointly with farmers. Indicators of the success of the work program which aims to develop the insight and skills of the community and farmers in improving the community economy with local microorganism entrepreneurship (MOL), and increasing the productivity of agricultural input products in Jubung village.